Experimental and numerical investigations of steel U-shaped dampers under vertical loadings for seismic mitigation - Zhang, Chao; Yu, Tianhao; Wang, Bin; Huang, Weiyuan; Zhong, Genquan; Zhao, Feng (Soil dynamics and earthquake engineering (1984), 2024)
Steel U-shaped dampers (UDs) are one of the earliest types of metallic energy dissipation devices. Previous studies have been conducted in past years to investigate the hysteretic behavior of steel UDs under in-plane and out-of-plane loadings. However, little attention has been paid to the working mechanism of the steel UDs under vertical loadings. The latter also has a wide range of application scenarios in the community of earthquake engineering. For this reason, this paper presents the mechanical properties of the steel UDs under vertical loadings. The analytical model of the steel UDs was developed first. Quasi-static cyclic tests were further conducted to investigate the hysteretic responses and fatigue behavior of the steel UDs. Experimental results revealed that the steel UDs can exhibit excellent energy dissipation capability, stable loading bearing capacity, and acceptable compression strength adjustment performance. Furthermore, the Manson–Coffin equation was developed to predict the fatigue behavior of the steel UDs with variational displacement amplitudes. Subsequently, the finite element numerical models of the steel UDs were developed to explore the UD's mechanical properties of practical interest in earthquake engineering. Parametric analysis results indicated that vertical preloads have an ignorable influence on the energy dissipation capability of the steel UDs. Moreover, the horizontal and vertical mechanical properties of the steel UDs can be considered as decoupled that could dissipate energy under multi-directional earthquakes. •The mechanical properties of steel U-shaped dampers under vertical loadings were explored for seismic mitigation.•The analytical equations of the dampers were developed and validated by experiments.•The Manson-Coffin equation of the dampers was proposed through fatigue tests.•Effects of vertical preloads and horizontal deformations on the vertical mechanical properties of dampers were discussed.